Malignant phosphaturic mesenchymal tumor with pulmonary metastasis: A case report. Issue 17 (April 2017) - Qiu, Shui; Cao, Li-Li; Qiu, Yue; Yan, Ping; Li, Zi-xuan; Du, Jiang; Sun, Li-Mei; Zhang, Qing-Fu
Abstract: Rationale: Phosphaturic mesenchymal tumor (PMT) is a new tumor entity of soft tissue and bone tumor recently accepted by the World Health Organization, which typically causes the paraneoplastic syndrome of tumor-induced osteomalacia (TIO). The majority of PMTs follow a benign clinical course and local recurrence occurs in < 10% of cases, malignant PMTs with distant organ metastasis are extremely uncommon. Patient concerns: We reported a 41-year-old woman who was diagnosed with PMT 10 years ago with a repeated recurrence and pulmonary metastasis. Diagnoses: Based on clinical manifestations, MRI scan, serum biochemical indicators evaluation, followed by histopathological examination, the patient was diagnosed as malignant PMT with pulmonary metastasis. Interventions: The patient was treated with calcium, phosphorus, and vitamin D after surgical resection and measured the serum ion concentrations every 3 months. Outcomes: The patient had a favorable outcome for 10 months without recurrence. Lessons: PMTs lack of characteristic histological morphology, some recurrence cases may appear benign morphologically; the malignant PMTs are easily overlooked. Patients with PMT should be carefully evaluated and monitored, in order to early identify its malignant potential.